Social Enclosure and L2 English Attrition in Acehnese Returnees - Fatayatul Hanani Safrul; Safrul Muluk (Journal of Innovation in English Education and Language Teaching, 2025)
This study examines the phenomenon of social enclosure and its relationship with second language (L2) English attrition among Acehnese returnees. Social enclosure refers to the limited interaction within close-knit local communities, which may reduce opportunities for sustained use of English after returning from abroad or other English-speaking environments. The research aims to analyze how reduced exposure, shifting social networks, and reintegration into local linguistic contexts contribute to the decline of English proficiency. A qualitative approach was employed, involving in-depth interviews and language use observations among Acehnese individuals who had previously acquired English as a second language. The findings reveal that strong reliance on the local language, minimal communicative need for English, and sociocultural adaptation significantly accelerate language attrition. Additionally, identity realignment and community expectations further discourage the active use of English in daily interactions. The study highlights the importance of maintaining language practice environments and supportive communities to mitigate L2 attrition. These findings contribute to broader discussions on language maintenance, sociolinguistics, and post-mobility language dynamics in multilingual societies.